PERANCANGAN FLYWHEEL HOLDER YANG ERGONOMIS UNTUK MEMPERCEPAT PROSES KERJA - Farrel, Ricky; Sukania, I Wayan; Utama, Didi Widya (Universitas Tarumanagara, 2025)
The high number of motorcycles in Indonesia increases the need for regular servicing, especially for the CVT system. However, the CVT servicing process in motorcycle repair shops still faces obstacles such as limited tools, the risk of injury due to component fitting, and low mechanical work efficiency. This study aims to design an ergonomic Flywheel Holder to improve comfort, safety, and work speed when removing CVT components. The design method uses the VDI 2221 approach for systematic design, TRIZ for design problem solving and ergonomic principles to adapt the tool to the mechanic's working conditions. Data were obtained through observation, interviews, Likert scale questionnaires, and time studies, and validity and reliability tests were conducted on data collection instruments. The results showed that the average temperature of the pulley during the service process reached 56.1℃, making it unsafe to touch directly by hand. The designed tool was proven to be able to hold the pulley stably, speed up the service process, and improve work safety. This design is the right solution to support the efficiency and ergonomics of motorcycle repair shops.